Computed Tomography Assessment of Ablation Zone Enhancement in Patients With Early-Stage Lung Cancer After Stereotactic Ablative Radiotherapy. Issue 5 (September 2015) - Moore, William; Chaya, Yair; Chaudhry, Ammar; Depasquale, Britney; Glass, Samantha; Lee, Susan; Shin, James; Mikhail, George; Bhattacharji, Priya; Kim, Bong; Bilfinger, Thomas
<x xml:space="preserve">Abstract</x> Introduction Stereotactic ablative radiotherapy (SABR) offers a curative treatment for lung cancer in patients who are marginal surgical candidates. However, unlike traditional surgery the lung cancer remains in place after treatment. Thus, imaging follow-up for evaluation of recurrence is of paramount importance. Materials and Methods In this retrospective designed Institutional Review Board-approved study, follow-up contrast-enhanced computed tomography (CT) exams were performed on sixty one patients to evaluate enhancement pattern in the ablation zone at 1, 3, 6, and 12 months after SABR. Results Eleven patients had recurrence within the ablation zone after SABR. The postcontrast enhancement in the recurrence group showed a washin and washout phenomenon, whereas the radiation-induced lung injury group showed continuous enhancement suggesting an inflammatory process. Conclusions The textural feature of the ablation zone of enhancement and perfusion as demonstrated in computed tomography nodule enhancement may allow early differentiation of recurrence from radiation-induced lung injury in patients' status after SABR or primary lung cancer.